2017
DOI: 10.1038/ijo.2017.154
|View full text |Cite
|
Sign up to set email alerts
|

A high salt diet inhibits obesity and delays puberty in the female rat

Abstract: Background/Objectives Processed foods are considered major contributors to the worldwide obesity epidemic. In addition to high sugar and fat contents, processed foods contain large amounts of salt. Due to correlations with rising adiposity, salt has recently been proposed to be obesogenic. This study investigated three hypotheses: i) high salt contributes to weight gain and adiposity in juvenile female rats, ii) puberty onset would be altered because salt is known to affect neuronal systems involved in activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 72 publications
5
14
2
Order By: Relevance
“…The relationship between high salt consumption and development of diabetes has not been established, and it appears its role in diabetes development has not been explored in previous studies. High salt diet has been demonstrated to aid increased lipid absorption in animal studies 36. In our study, however, we found a strong association between high salt diet intake with BMI and WC, possibly suggesting that BMI and WC may mediate the association between high salt intake and diabetes.…”
Section: Discussioncontrasting
confidence: 80%
“…The relationship between high salt consumption and development of diabetes has not been established, and it appears its role in diabetes development has not been explored in previous studies. High salt diet has been demonstrated to aid increased lipid absorption in animal studies 36. In our study, however, we found a strong association between high salt diet intake with BMI and WC, possibly suggesting that BMI and WC may mediate the association between high salt intake and diabetes.…”
Section: Discussioncontrasting
confidence: 80%
“…Although high-salt diets have been suggested to be obesogenic (e.g., [3,8,23] see introduction), our results are consistent with many other studies that show high-salt diets do not increase body weight or adiposity (e.g., [24][25][26][27]).…”
Section: Discussionsupporting
confidence: 91%
“…While the variations of perigonadal white adipose tissue (WAT) weight as well as WAT/body weight ratios were related to dietary copper content in male rats, they were more likely to be affected by dietary fructose in female rats. The energy efficiency ratio (EER, %), i.e., the ratio of body weight gain and total energy intake [ 54 , 55 ], was decreased by dietary fructose in both male and female rats compared to their controls, suggesting the metabolic effects of fructose may not be contributed to the calorie intake. Ad libitum feeding of fructose via drinking water led to a significant increase in water intake and a decrease in pellet food intake.…”
Section: Resultsmentioning
confidence: 99%